DBU-promoted Cu(OAc)2·H2O-catalysed coupling reactions of aryl iodides and sodium azide. (1st June 2018) - Jiang, Yuqin; Suo, Huajun; Zhao, Yaru; Li, Xiyong; Sun, Yamin; Li, Xingfeng; Dong, Wenpei; Li, Wei; Zhang, Weiwei; Xu, Guiqing
An efficient and simple protocol for the synthesis of aryl azides by the coupling of aryl iodides with sodium azide, in good to excellent yields in DMSO at 95 ºC under catalysis by Cu(OAc)2·H2O and 1, 8-diazabicyclo[5.4.0]undec-7-ene (DBU), has been established. The optimised loadings of Cu(OAc)2·H2O and DBU were 10 mol% and 15 mol% respectively.